Investigation of thermal-mechanical performance of dual-chip SiC power devices based on Cu clip interconnection - LIAO Linjie; FAN Yi; MEI Xiaoyang; WANG Liancheng (机车电传动)
Traditional packaging structures of power semiconductor device use aluminum (Al) wire for bonding. This leads to high parasitic inductance and reliability issues, limiting the development of silicon carbide (SiC) power devices. Researchers have proposed a new copper clip interconnection process that enables double-sided heat dissipation and improves the power density of the devices. However, current research mainly focuses on its thermal performance and reliability, lacking exploration of structural design optimization. Further research is necessary to optimize the structure design of multi-chip copper clip interconnections. This study investigated the influence of critical structural parameters of the copper clip power devices on chip stress concentration through simulations. The results indicate that the copper clip thickness has the most significant impact on chip stress concentration, while the copper clip span has the least influence. Optimal structural parameter which was compared with the smallest solder layer stress were used to establish a copper clip device model and the corresponding wire-bonded module. The findings reveal that, under power cycling, the copper clip device shows a more than 10 times improvement in the fatigue life of both the copper clip and solder layer compared with the wire-bonded module. And the unloading groove significantly helps improve the fatigue life of copper clip devices.